Alcoholization as an Alternative Treatment for Prostatic Cyst and Abscess in Dogs - Giulia Ballotta; Giuseppe Spinella; Marco Cunto; Daniele Zambelli (Animals)
Current therapeutic approaches for prostatic cysts and abscesses involve surgical methods like reduction and omentalization. This retrospective study evaluates the effectiveness and safety of ultrasound-guided percutaneous drainage combined with alcoholization as a minimally invasive treatment for prostatic cysts and abscesses in dogs. Forty-three male dogs with a single prostatic cavity (1–6 cm) were enrolled and categorized into two groups: group A (twenty-two dogs with prostatic abscesses treated via alcoholization) and group B (twenty-one dogs with BPH-associated cysts). Group B was further subdivided into three subgroups: B1 (finasteride only), B2 (alcoholization only), and B3 (combined finasteride and alcoholization). Alcoholization involved sedation, drainage of the cavity, and two ethanol instillations (first: 1/3–1/4 of aspirated volume; second: 1/10 after 25 min). Ultrasound evaluations were performed at scheduled intervals of up to 150 days. In group A, 76.19% of abscesses were resolved within 30 days, with complete resolution in all dogs by day 150. In group B, the combined treatment (group B3) showed superior outcomes, with significant cyst diameter reduction observed in all dogs within 30 days and complete resolution in 62.5% by day 150. These findings support alcoholization as an effective, low-complication alternative to surgery for selected prostatic lesions in dogs.